Which equation is equivalent to the formula below? y = a(x – h)^2 + k Question Which equation is equivalent to the formula below?y = a(x – h)^2 + k in progress 0 Math Ivy 1 week 2021-11-26T03:47:19+00:00 2021-11-26T03:47:19+00:00 2 Answers 0

## Answers ( )

The photo provided by me has the answer attached.

Answer:See below.

Step-by-step explanation:The given equation is in vertex form. We can convert it to standard form as follows:

y = a(x – h)^2 + k

y = a(x^2 – 2hx + h^2) + k

y = ax^2 – 2ahx + (ah^2 + k)(answer).